Taiwanese Student Attitudes Towards Error Correction and Written Corrective Feedback in L2 Writing Classes - David R. Berg; Yichen Lu (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2017)
Error correction and corrective feedback in L2 writing has long been an important issue for EFL teachers and researchers, as well as EFL students. This study aimed to examine a population of Taiwanese EFL writing students to assess their attitudes and preferences for corrective feedback in their English writing. This study utilized a 31-question self-report survey to gather data from 79 EFL writing students. Results indicate that most students felt it was very important for the teacher to provide comprehensive direct or indirect coded feedback on all types of errors, but mostly on grammatical errors. The findings hold important implications for EFL writing teachers in Taiwan. EFL writing teachers should have open dialogues with their students in order to determine the most beneficial form of feedback for each class.